2002
DOI: 10.1080/10915810290096469
|View full text |Cite
|
Sign up to set email alerts
|

Oral (Gavage) Two-Generation (One Litter Per Generation) Reproduction Study of Pentachlorophenol (Penta) in Rats

Abstract: The potential for pentachlorophenol (penta) to induce general and reproductive/developmental toxicity was evaluated in Crl Sprague-Dawley rats, employing a two-generation reproduction toxicity study. Penta was administered by gavage at doses of 0, 10, 30, and 60 mg/kg/day. In both generations, the parental animals (30/sex/group) were intubated daily for 10 weeks before cohabitation and continuing through cohabitation, gestation, and lactation periods. Intubation of the F1 generation was begun 28 days postpartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In our study, however, developmental PCP treatment did not affect plasma ir-inhibin, plasma testosterone, plasma LH, plasma FSH, or sperm production. In contrast, neonatal high-dose PCP treatment (30 or 60 mg kg -1 day -1 ) led to small testes, decreased spermatid count, and delayed sexual maturation in rats [57]. However, this reproductive disability in animals given high-dose PCP may be attributable to toxicity, in light of concurrent induced liver weight with histopathologic toxicity, reduced body weight, and reduced feed consumption.…”
Section: -Wk-oldmentioning
confidence: 78%
“…In our study, however, developmental PCP treatment did not affect plasma ir-inhibin, plasma testosterone, plasma LH, plasma FSH, or sperm production. In contrast, neonatal high-dose PCP treatment (30 or 60 mg kg -1 day -1 ) led to small testes, decreased spermatid count, and delayed sexual maturation in rats [57]. However, this reproductive disability in animals given high-dose PCP may be attributable to toxicity, in light of concurrent induced liver weight with histopathologic toxicity, reduced body weight, and reduced feed consumption.…”
Section: -Wk-oldmentioning
confidence: 78%
“…These conclusions were based upon the fact that the NOAELs for general toxicity and developmental toxicity were the same and the LOAELs for general toxicity and developmental toxicity were the same. Speci cally, (1) the LOAEL for maternal toxicity (e.g., reduced body weights, organ weights, and food consumption) and expected maternal metabolic effects (e.g., increased liver weights, heptaocellular centrilobular hypertrophy, and vacuolation) was the middle dose tested (30 mg/kg/day), as was the LOAEL for developmental toxicity (i.e., reduced pup weights and viability), and (2) the NOAEL was the lowest dose tested (10 mg/kg/day), as was the NOAEL for developmental toxicity (Bernard et al 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…These studies included one that evaluated reproduction in a multigeneration rodent study and two that evaluated developmental toxicity, one in the rodent (rat) and one in the nonrodent (rabbit). In the multigeneration study, it was concluded that penta was not a reproductive toxicant because the LOAEL and the NOAEL (10 and 30 mg/kg/day, respectively) were the same for reproductive effects and general toxicity (Bernard et al 2001a). In the rat developmental study, penta was not a selective developmental toxicant because the no-observable-effec t (NOEL) for both general toxicity in the dam and developmental effects in the fetus was 30 mg/kg/day (Bernard, Ranpuria, and Hoberman 2001b).…”
mentioning
confidence: 99%
“…Rams exposed to PCP displayed atrophy of seminiferous tubules as well as decreased spermatocytes production (Beard et al ., ). Similarly, PCP induced delayed sexual maturation, low spermatid counts and reduced testes weight in rats (Bernard et al ., ).…”
Section: Toxicants Affect Male Reproductive Function By Impairing Sermentioning
confidence: 99%